Modifiable and Nonmodifiable Predictive Factors Associated with the Outcomes of Total Knee Arthroplasty - Bonasia, Davide E.; Palazzolo, Anna; Cottino, Umberto; Saccia, Francesco; Mazzola, Claudio; Rosso, Federica; Rossi, Roberto (Joints, 2019)
Total knee arthroplasty (TKA) is a valuable treatment option for advanced osteoarthritis in patients unresponsive to conservative treatments. Despite overall satisfactory results, the rate of unsatisfied patients after TKA remains high, ranging from 5 to 40%. Different modifiable and nonmodifiable prognostic factors associated with TKA outcomes have been described. The correction, whenever possible, of modifiable factors is fundamental in preoperative patients' optimization protocols. Nonmodifiable factors can help in predicting the outcomes and creating the right expectations in the patients undergoing TKA. The goal of this review is to summarize the modifiable and nonmodifiable prognostic factors associated with TKA outcomes.
Keywords: total knee arthroplasty; predictive factor; prognostic factor; outcome; patient optimization